Rice market information transfer system (mits) in the Mekong delta, Vietnam? - Nghiep, Pham Cong (Studia Mundi – Economica, 2018)
MITS had an important role in farmers’ production and trade. However, MITS in the Mekong delta, Vietnam was very weak. There were lacks of good sources and channels of market information, the market information was outdated, inaccurate and inadequate. In addition, farmers’ ability and knowledge to collect, analyze and use market information were also limited. Therefore, the aims of the paper are to have a real clear picture about the current MITS in the rice value chain in the Mekong delta of Vietnam (rice farmer’s demands of rice market information, sources of rice market information, channels of rice market information, rice market information utilization and impacts of MITS on rice farmers in the Mekong delta, Vietnam). This paper gives an overview about 15 structural interviews made with 15 rice farmers in the Mekong delta, Vietnam. The findings of this study show that rice farmers in the Mekong delta, Vietnam have been accessing and using market information from formal and informal sources (Governmental agencies, traders, farmers, and mass media) via 7 main channels (Television, newspaper, radio, Internet, phone, face-to-face meetings, loudspeaker) to increase the selling prices, rice income, to decrease the risks in rice production and trade and to improve negotiation ability of farmers with traders.
Keywords: Rice production; market information; farmers; qualitative study; Vietnam